Analysis and Application of Metro Pantograph Dynamic Envelope - DENG Bo (Chengshi guidao jiaotong yanjiu)
Objective Safe operation of the catenary system in metro power supply system highly relies on the rational design of the pantograph dynamic envelope, the industry has not yet established a unified method and parameters for determining the pantograph dynamic envelope. Therefore, it is particularly important to conduct in-depth research on the determination of pantograph dynamic envelope parameters under different speed levels. Method The definitions of the dynamic envelope in existing specifications are analyzed and their ambiguity in the application in metro field is pointed out. By analyzing the mathematical model of the pantograph swing value in European and German standards in-depth, combined with the actual parameters of metro catenary design, an evaluation method for the maximum lateral swing value of metro pantograph under different operation conditions is proposed. Result & Conclusion The lack of unified standards for China's metro pantograph dynamic envelope has a significant impact on the safety of catenary design, as well as construction, maintenance, and other aspects. In view of this situation, it is expected that during the "14th Five-Year Plan" period, through the joint efforts of industry associations, vehicle manufacturers, design unites and construction units, and with the development of standard metro trains, a unified and accurate standard for pantograph dynamic envelope in China can be formulated to promote the high-quality development of rail transit industry.